2022
DOI: 10.1016/j.pedn.2021.06.024
|View full text |Cite
|
Sign up to set email alerts
|

YouTube as a source of information about COVID-19 for children: Content quality, reliability, and audience participation analysis

Abstract: This study aimed to evaluate the content quality, reliability, and audience participation analysis of YouTube videos as a source of information about COVID-19 for children. Design and methods: This study was conducted in a descriptive design. The keywords "COVID-19, explain, children" were searched on the YouTube platform on March 17, 2021, and 294 videos were reviewed. The content of the selected videos was analyzed by 2 independent reviewers. Meet the inclusion criteria, 57 videos were evaluated according to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 36 publications
2
14
0
3
Order By: Relevance
“…Studies in the literature point out that the sources of YouTube videos are diverse and the quality of videos varies with the source. A study by Azak et al (2022) evaluated YouTube videos on COVID-19 in children and, in line with the results of our study, found that DISCERN scores were higher in videos uploaded by academic sources and lower in news videos; they found the difference to be statistically significant. Similarly, Li et al (2020) evaluated YouTube videos on COVID-19 and found that, entertainment news videos had low reliability and quality than government/Professional videos, along with low DISCERN and JAMA scores.…”
Section: Discussionsupporting
confidence: 90%
“…Studies in the literature point out that the sources of YouTube videos are diverse and the quality of videos varies with the source. A study by Azak et al (2022) evaluated YouTube videos on COVID-19 in children and, in line with the results of our study, found that DISCERN scores were higher in videos uploaded by academic sources and lower in news videos; they found the difference to be statistically significant. Similarly, Li et al (2020) evaluated YouTube videos on COVID-19 and found that, entertainment news videos had low reliability and quality than government/Professional videos, along with low DISCERN and JAMA scores.…”
Section: Discussionsupporting
confidence: 90%
“…Policy and regulatory responses that reduce economic and structural drivers of false or misleading content. These include competition measures, as have been seen in Australia (Australian Competition and Consumer Commission, 2020 [109]) and France (Autorité de la concurrence, 2020 [110]); promoting quality and safety in platform design that, for example, promote the development of tests, standards and processes to support responsible business conduct and promote safety and quality of digital services (Forum on Information and Democracy, 2020 [111]); and promoting and maintaining a diverse and independent media sector through anti-monopoly measures and fostering fair competition.…”
Section: Policy Context Of Media Literacymentioning
confidence: 99%
“…Penggunaan Azak, Şahin, Korkmaz, & Yıldız, 2021). Golongan muda juga lebih mudah untuk mengekspresikan pandangan mereka menggunakan video (Ying & Baboo, 2015).…”
Section: Perbincangan Kajianunclassified